Measurements & instrumentation - Bhavani, V.; Vasantha, S. (Electrical engineering, 2008)
The text is written in simple and lucid language, with the aim of giving a comprehensive understanding of the various principles and application about the topic. Important equations are shown and explained in this book through examples. Topics include : Classification and Characteristics of Instrumentation ; Measurement of Voltage, Current and Resistance; Measurement of Power and Energy; Special Instruments and Bridges and Transducers and Industrial Instrumentation